Thermodynamic analysis of heat-energized refrigeration machine with carbon dioxide - Морозюк, Татьяна Владиленовна; Гайдук, Сергей Васильевич; Морозюк, Лариса Ивановна (Eastern-European Journal of Enterprise Technologies, 2014)
The stages of creating a circuit-cycle design of a heat-energized refrigeration machine using carbon dioxide as a working fluid are considered in the paper. The purpose of the machine development is to get cold using a low-temperature heat of enterprises, as a way of saving energy and material resources. The thermodynamic analysis for generating a machine circuit using the "cycle method", the energy and exergy analysis of parts and the machine in general, in a wide range of temperatures and pressure in the gas heater, was conducted. The analysis showed that the machine can work in a wide range of the heating source and different pressures in the gas heater, but their change affects the effectiveness of other machine parts, which affects the exergy efficiency of the machine and its parts. The obtained results of the analysis are useful for further implementation of the machine, namely modeling, design and selection of machine parts for the maximum efficiency.